Cerebral Arterial Pulsatility and Global White Matter Microstructure Impact Spatial Working Memory in Older Adults With and Without Cardiovascular Risk Factors - Conley, Alexander C.; Karayanidis, Frini; Jolly, Todd A. D.; Yang, Meng-Heng; Hsieh, Shulan (Frontiers in Aging Neuroscience, 2020)
Aging is associated with increased prevalence of vascular health conditions. These are associated with changes in the cardiac vasculature and detrimental changes to cerebral structure and function, most strikingly in cerebral white matter. Previous research has shown that increased arterial pulsatility is related to decreased white matter microstructural organization and impaired cognitive functioning. However, this relationship was only significant in people with cardiovascular risk factors. Conversely, the absence of cardiovascular risk factors is thought to relate to better long-term cognitive health. This study aimed to test this hypothesis by examining the relationship among arterial pulsatility, white matter microstructural organization and working memory capacity in younger and older adults. We then further examined whether the age-related differences in the relationship among these variables, if found, varied as a function of the presence of cardiovascular risk factors for the elderly. A total of 92 older adults (44 male, with and without cardiovascular risk factors: CV+, CV-) and 97 younger adults (57 male) participated in this study. Arterial pulsatility and the whole brain diffusion tensor imaging indexes (fractional anisotropy (FA), radial diffusivity (RaD), and mean diffusivity (MD)) were measured. Cognitive function was assessed as sensitivity (d’) from a 2-back task. To examine the direct and indirect effects of arterial pulsatility, white matter health and cognition, we ran mediation models with arterial pulsatility as the predictor of cognitive performance and MD or RaD as the mediator. Results showed no association between arterial pulsatility, global white matter health and cognition in the younger adults. In older adults, poor white matter health was associated with increased arterial pulsatility and worse working memory performance. The mediation models showed and significant indirect effect of arterial pulsatility on 2-back d’ via MD or RaD. When we divided the older adults into their cardiovascular risk subgroups, it was revealed that these indirect effects were only present in the CV+ subgroup, not the in the CV- subgroup. These findings highlight that impact of cardiovascular risk factors and arterial pulsatility on white matter health and working memory performance in cognitively normal older adults.